2011
DOI: 10.1007/s12600-011-0161-9
|View full text |Cite|
|
Sign up to set email alerts
|

Note on Wahlgreniella nervata (Gillette, 1908) (Hemiptera: Aphididae): a new pest of Damask rose in Turkey

Abstract: Alate viviparous females of Wahlgreniella nervata (Gillette) were found on a Damask rose (Rosa damascena Mill.) plantation in Isparta Province, Turkey. The aphid is recorded for the first time from Turkey. Besides, Damask rose is a new host for this species. Brief information about this aphid including a key to the alate females of aphid species known to infest Damask rose in Turkey is provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Of the 28 subfamilies identified (total 4700 species) in the world (Remaudiere and Remaudiere, 1997;Fraval, 2006;Turpeau-Ait Ighil et al, 2011), 450 species have been identified on cultivated plants (Blackman and Eastop, 2000). In Algeria, according to Laamari et al (2010) and Aroun (2015), Rosaceae, Asteraceae, Poaceae and Solanaceae are the most infested host plant W. nervata is an american species, introduced to Europe and first reported in England in 1973 on roses (Barjadze et al, 2011). In North America, the species is apparently heteroecious, with host alternation between primary host roses and secondary host Ericaceae (Arbutus, Arctostaphylos, Pieris).…”
Section: Introductionmentioning
confidence: 99%
“…Of the 28 subfamilies identified (total 4700 species) in the world (Remaudiere and Remaudiere, 1997;Fraval, 2006;Turpeau-Ait Ighil et al, 2011), 450 species have been identified on cultivated plants (Blackman and Eastop, 2000). In Algeria, according to Laamari et al (2010) and Aroun (2015), Rosaceae, Asteraceae, Poaceae and Solanaceae are the most infested host plant W. nervata is an american species, introduced to Europe and first reported in England in 1973 on roses (Barjadze et al, 2011). In North America, the species is apparently heteroecious, with host alternation between primary host roses and secondary host Ericaceae (Arbutus, Arctostaphylos, Pieris).…”
Section: Introductionmentioning
confidence: 99%
“…Myzaphis rosarum (Kaltenbach, 1843) and M . turanica Nevsky, 1929 are pests of the cultivated rose [ 5 ]. Five species— M .…”
Section: Introductionmentioning
confidence: 99%
“…Vučetić et al 2014) and the alien ones (e.g. Barjadze & Ben-Dov 2011;Barjadze et al 2011b;Hałaj et al 2011). The reason for this can be the introduction through plant trade, now intensified and sometimes uncontrolled in terms of pest control (Hałaj et al 2011).…”
mentioning
confidence: 99%
“…These two aspects together result in the fact that aphids can cause significant damage to crops or lower plants' commercial value (e.g. Barjadze et al 2011a;Hałaj & Osiadacz 2013); hence every new pest should be reported and monitored. A. vitalbae was observed to cause premature drying of leaf ends and the deformation of young shoots if it infested the bottom part of clematis leaves in large colonies (30-50 individuals).…”
mentioning
confidence: 99%